Diagnostic value of neutrophil to lymphocyte ratio and serum biomarkers in chronic osteomyelitis - Wenhui Zhao; Dongxiang Xu; Yanbin Dong; Wanwen Feng (Scientific Reports)
Abstract Chronic osteomyelitis (COM) is a persistent bone infection associated with severe complications, making early and accurate diagnosis essential. Traditional diagnostic methods, including imaging and bacterial cultures, are often limited by low sensitivity, long processing times, and the inability to detect infections in certain clinical scenarios. In this study, we evaluated the diagnostic utility of inflammatory biomarkers for COM, including neutrophil to lymphocyte ratio (NLR), C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6). A total of 200 participants, including 100 COM patients and 100 healthy controls, were enrolled. Our results showed that Gram-positive bacteria were more prevalent (59%), with Staphylococcus aureus being the most frequently isolated pathogen. Antibiotic resistance profiling revealed that Gram-positive bacteria exhibited high resistance to Penicillins but remained sensitive to Vancomycin and Linezolid. In contrast, Gram-negative bacteria showed high resistance to certain Penicillins, while sensitive to Carbapenems. Inflammatory marker levels (NLR, CRP, TNF-α, and IL-6) were significantly elevated in COM patients, with higher levels in Gram-negative infections. Multivariate logistic regression analysis and ROC curve analysis demonstrated that these inflammatory markers were significant predictors of COM, and the combination of these biomarkers showed superior diagnostic performance. Our findings suggest that NLR, CRP, TNF-α, and IL-6 are valuable diagnostic biomarkers for COM, and their combination enhances diagnostic precision, offering a promising tool for clinical management.